1996
DOI: 10.1038/379557a0
|View full text |Cite
|
Sign up to set email alerts
|

Role of transactivation of the EGF receptor in signalling by G-protein-coupled receptors

Abstract: Transduction of a mitogenic signal from the cell membrane to the nucleus involves the adapter proteins SHC and Grb2, which mediate activation of the Ras/mitogen-activated protein (MAP) kinase pathway. In contrast to receptor tyrosine kinases (RTKs), the signalling steps leading to Ras/MAP kinase activation by G-protein-coupled receptors (GPCRs) are still poorly characterized but appear to include beta gamma subunits of heterotrimeric G-proteins and as-yet unidentified tyrosine kinases. We report here that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
1,035
3
6

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,384 publications
(1,091 citation statements)
references
References 29 publications
39
1,035
3
6
Order By: Relevance
“…Delayed injection of the GST-Shc SH2 into thrombin stimulated astrocytoma cells results in a time course of inhibition similar to that observed with EGF-stimulated fibroblasts (Ricketts et al, 1996). Ullrich's group recently reported that EGFR are activated in response to thrombin stimulation of Rat1 ®broblasts (Daub et al, 1996). The mitogenic inhibition following microinjection of the GST-Shc SH2 in 1321N1 cells could therefore result from inhibition of an EGFR signaling component.…”
Section: Discussionmentioning
confidence: 54%
“…Delayed injection of the GST-Shc SH2 into thrombin stimulated astrocytoma cells results in a time course of inhibition similar to that observed with EGF-stimulated fibroblasts (Ricketts et al, 1996). Ullrich's group recently reported that EGFR are activated in response to thrombin stimulation of Rat1 ®broblasts (Daub et al, 1996). The mitogenic inhibition following microinjection of the GST-Shc SH2 in 1321N1 cells could therefore result from inhibition of an EGFR signaling component.…”
Section: Discussionmentioning
confidence: 54%
“…Interestingly, tissue-speci®c expression of activated Ga i2 (Ga i2 Q205L) mimicked the actions of insulin, thus further supporting a`permissive' role for Ga i2 in insulin-receptor signaling pathway . Recently it has been shown that the stimulation of receptors for endothelin, thrombin, and LPA transactivate EGFR and this transactivation is necessary for the activation of ERK activation, fos gene expression, and DNA synthesis suggesting the critical role played by EGFR in G protein mediated signaling (Daub et al, 1996). Such interactions between di erent Gasubunits and other signaling cascades such as those between Ga i1 and TGFbR (Kataoka et al, 1993), Ga i and bFGFR (Sa and Fox, 1994), Ga q and PDGFR (De Vivo and Iyengar, 1994), Ga i2 and CSF-1R (Corre and Hermouet, 1995), Ga 13 and IGF-1R (Liu et al, 1997) and Ga 13 and EGFR (Gohla, 1998) have been identi®ed.…”
Section: G Protein Interactions With Other Signaling Pathwaysmentioning
confidence: 99%
“…Numerous, recent reports have shown that transactivation of the epidermal growth factor (EGF) receptor (EGFR) is critical for the mitogenic activity of multiple GPCR agonists (Daub et al, 1996(Daub et al, , 1997Prenzel et al, 1999;Madarame et al, 2003;Xiao et al, 2003;Zhao et al, 2004) and that EGFR transactivation requires metalloproteinase (MMP) cleavage of pro-heparin-binding EGF-like growth factor (pro-HB-EGF) into HB-EGF, which is released from the cell surface to bind the EGFR in an autocrine or paracrine manner (Prenzel et al, 1999;Madarame et al, 2003;Santiskulvong and Rozengurt, 2003;Yano et al, 2004;Zhao et al, 2004;Hassan and Carraway, 2006). However, the detailed signaling events following EGFR transactivation that are required for mitogenic activation are not fully understood, particularly in prostate cancer cells.…”
Section: Introductionmentioning
confidence: 99%